My happy marriage. 4 - Agitogi, Akumi (Square Enix Manga, 2023)
A Cinderella-inspired, slow-burn historical romance with a paranormal twist set in Taisho-era Japan! A browbeaten and mistreated daughter is cast out of her home and sent to audition as a bridal candidate for the heir to one of the most powerful families in the land... For failing to inherit the boon of unusual power that is the Saimori birthright and bringing shame to the family name, mistreated Miyo is cast out to become another's problem. Sent to the Kudo clan--itself preternaturally powerful--as a potential bride for its heir, Kiyoka, Miyo is surprised to experience kindness for the first time in her thus far sad life. Though the rumors make him out to be cold and haughty, Kiyoka Kudo quickly warms up to the Saimoris' eldest daughter. Intrigued by the girl who stands worlds apart from the spoiled, social-climbing women who usually vie for his hand, Kiyoka soon comes to regard Miyo with affection. Suddenly, Miyo and Kiyoka encounter a mysterious man named Arata Tsuruki. What does he want, and what connection does he have to the enigmatic and powerful Usuba clan that Miyo's mother hailed from?